2016
DOI: 10.1155/2016/8760592
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Used Tire Cushion Layer under Rockfall Impact

Abstract: Rock shed is widely used in traffic lines against rockfall. In order to cushion rockfall impact and dissipate impact energy, cushion layer is usually adopted in rock shed. Used tire cushion layer is proposed in this paper and it can cushion rockfall impact utilizing large radial deformation of tire. Reinforced concrete structure model is built with used tire cushion layer and artificial rockfall test is carried out. Twelve tests are divided into 4 sets with different rockfall mass, rockfall height, and tire fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Considering equations (22), (19), and 14, we obtain Taking the boundary conditions r � r q and σ r � σ rq into account, we obtain…”
Section: Mechanical Analysis Of the Elastic Zonementioning
confidence: 99%
See 1 more Smart Citation
“…Considering equations (22), (19), and 14, we obtain Taking the boundary conditions r � r q and σ r � σ rq into account, we obtain…”
Section: Mechanical Analysis Of the Elastic Zonementioning
confidence: 99%
“…Yuan et al analyzed the influence of the weight, shape, falling height, and impact angle of rockfall on the impact force based on experiments [21]. Sun et al attempted to add discarded tires to the soil cushion layer and investigated the impact resistance of the new cushion structure via an experimental approach [22]. Zhang et al investigated the mechanical response mechanism of oil/gas pipe under rockfall impact using a numerical simulation method [23].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in high-speed railway engineering, rubber bearings were used as resilient elements to reduce train-induced vibrations transmitting to surrounding areas [10,11]. In similar scenarios of shelters subjected to rockfall impacts, the dynamic response of the shelters can be significantly reduced when sand cushion or used tire cushion layers were applied [12,13].…”
Section: Tube Assemblymentioning
confidence: 99%
“…Wang et al [12] and Zarnani and Bathurst [13] also studied the buffering performance of expanded polystyrene (ESP) in civil air defence engineering and retaining wall projects. Sun et al [14] studied the buffering performance of a rubber tire cushion using 12 impact tests; they reported that rubber tires can significantly reduce the impact force, and the buffering performance will be further enhanced when the tire is filled with sand or gravel. Hsu et al [2,3] studied the impact resistance of a composite cushion made of EPS, a steel grille, and steel wire meshes; they found that in comparison to sand cushion, the composite cushion reduced the maximum impact force by 50%.…”
Section: Introductionmentioning
confidence: 99%